2008
DOI: 10.1007/s10404-008-0369-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of laminar-to-turbulent transition for isothermal gas flows in microchannels

Abstract: In this work the laminar-to-turbulent transition in microchannels of circular cross-section is studied experimentally. In order to single out the effects of relative roughness, compressibility and channel length-to-diameter ratio on the Reynolds number at which transition occurs, experimental runs have been carried out on circular microchannels in fused silica-smooth for all purposes-and in stainless steel (which possess a high surface roughness), with a diameter between 125 and 180 lm and a length of 5-50 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…It is reported that the transition occurred in the Reynolds number range of 1980e2600 for the re-entrant inlet, 2070e2800 for the square-edged inlet and 2125e3200 for the bell-mouth inlet for isothermal conditions, and it changed depending on heat flux in the case of non-isothermal flow. On the other hand, several investigators remarked the dependence of critical Reynolds number on the surface roughness and geometry [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the transition occurred in the Reynolds number range of 1980e2600 for the re-entrant inlet, 2070e2800 for the square-edged inlet and 2125e3200 for the bell-mouth inlet for isothermal conditions, and it changed depending on heat flux in the case of non-isothermal flow. On the other hand, several investigators remarked the dependence of critical Reynolds number on the surface roughness and geometry [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that the slight decrease in the transition range may be due to the relative roughness or the edge effects of the trapezoidal channel geometry. Morini et al [11] studied the laminar to turbulent transition in the fused silica and stainless steel microtubes having the diameters ranging from 0.125 to 0.180 mm, using nitrogen as working fluid. They reported that the transitional regime started at the Reynolds numbers around 1800e2000, and the surface roughness had no effect on the hydraulic resistance in the laminar region for a relative roughness lower than 4.4%, taking compressibility into account.…”
Section: Introductionmentioning
confidence: 99%
“…Before conducting the numerical simulation process, we calculated that the Re number in the channel was about 2500 with the minimum velocity of the jet inlet being 2.74 m/s. Extensive research reports indicated that the classical transition values from laminar to turbulent flow regime are 1000-2500 Rands et al, 2006;Tang et al, 2007;Morini and Lorenzini, 2009). All these results were found with clear microtubes being the test sections.…”
Section: Computational Proceduresmentioning
confidence: 99%
“…Moreover, the annular flow patterns always accompany with interfacial waviness at the gas phase superficial velocities of 27.8 m/s or 83.3 m/s. The waviness can change the crossing area that gas phase passes by and induce instabilities to the gas flow, which may cause the transition from laminar to turbulent flow at a smaller gas phase Reynolds number [30,31]. The gas phase Reynolds number in Fig.…”
Section: Flow Pattern Analysismentioning
confidence: 99%